2022
DOI: 10.3390/antibiotics11121795
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retail Meat as a Source of ESBL Escherichia coli in Tamaulipas, Mexico

Abstract: In recent decades, the appearance of a group of strains resistant to most β-lactam antibiotics, called extended-spectrum β-lactamases (ESBLs), has greatly impacted the public health sector. The present work aimed to identify the prevalence of ESBL-producing Escherichia coli strains in retail meat from northeast Tamaulipas. A total of 228 meat samples were obtained from 76 different stores. A prevalence of E. coli ESBL of 6.5% (15/228) was detected. All (15/15) of the ESBL strains were multiresistant. Altogethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…E. coli can be classified into four main phylogenetic groups named A1, B1, B2, and D, which can be identified by PCR of four genes [ 6 ]. Generally, commensal strains belong to groups A1 and B1, while most virulent strains belong to groups B2 and D [ 6 , 61 ]. In the present study, all the isolates were of the commensal groups A (6.2%) and B1 (93.8).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…E. coli can be classified into four main phylogenetic groups named A1, B1, B2, and D, which can be identified by PCR of four genes [ 6 ]. Generally, commensal strains belong to groups A1 and B1, while most virulent strains belong to groups B2 and D [ 6 , 61 ]. In the present study, all the isolates were of the commensal groups A (6.2%) and B1 (93.8).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all the isolates were of the commensal groups A (6.2%) and B1 (93.8). Previous studies have also reported that the majority of the E. coli phylotypes from different sources were of the commensal groups A1 and B1 [ 61 – 63 ]. In Egypt, Abdallah, et al [ 64 ] reported that 80% of ESBL-producing E. coli isolated from chicken meat in the same study area were also of the commensal groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations